2022
DOI: 10.1155/2022/1116923
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining and Network Pharmacology Analysis of Kidney-Tonifying Herbs on the Treatment of Renal Osteodystrophy Based on the Theory of “Kidney Governing Bones” in Traditional Chinese Medicine

Abstract: Background. Renal osteodystrophy (ROD) secondary to chronic kidney disease is closely associated with osteoporosis and fractures. Based on the theory of “kidney governing bones” in traditional Chinese medicine (TCM), treating bone diseases from the perspective of the kidney has become a basic principle of treating ROD. However, there are many kidney-tonifying herbs and their mechanisms of treating ROD are not clear. Therefore, our study intends to use data mining and network pharmacology to study the commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…On basis of the theory of ‘Kidney Governing Bones’ in TCM, Chinese herbal medicines for tonifying kidney and strengthening bone have been applied in clinical treatment of bone repair, 7 especially Epimedium brevicornum maxim and Curculigo orchioides Gaertn. The findings suggested that the main active substances of Epimedium were flavonoids, such as Icariin, Epimedin A/B/C, Baohuoside I and so on, which could regulate the activities of osteoblasts, accelerate the fracture healing and promote the balance of bone metabolism 8–10 .…”
Section: Introductionmentioning
confidence: 99%
“…On basis of the theory of ‘Kidney Governing Bones’ in TCM, Chinese herbal medicines for tonifying kidney and strengthening bone have been applied in clinical treatment of bone repair, 7 especially Epimedium brevicornum maxim and Curculigo orchioides Gaertn. The findings suggested that the main active substances of Epimedium were flavonoids, such as Icariin, Epimedin A/B/C, Baohuoside I and so on, which could regulate the activities of osteoblasts, accelerate the fracture healing and promote the balance of bone metabolism 8–10 .…”
Section: Introductionmentioning
confidence: 99%
“…Psoraleae Fructus (also termed as "Bu-Gu-Zhi" in Chinese, PF) is the dried matured seeds of the leguminous plant Psoralea corylifolia L., which has been used to treat osteoporosis, arthralgia, vitiligo and other diseases in Asian countries for a long history [4][5][6] . According to the statement in Compendium of Materia Medica, PF is believed to show good therapeutic effect of warming and tonifying the Kidney-Yang, gathering spirit and enriching the bone marrow 7 . Modern pharmacological researches have manifested the extracts of PF exhibited anti-tumor, antioxidant, antimicrobial, anti-in ammatory and antidepressive activities 8-10 .…”
Section: Introductionmentioning
confidence: 99%